High-strength catalyst carrier and preparation method thereof

By using nanosilicon dioxide and modified graphene oxide to form a crosslinking network, the problem of low molecular sieve molding strength is solved, the preparation of high-strength catalyst support is realized, and the mechanical strength and activity of the support are improved.

CN119680619AInactive Publication Date: 2025-03-25ZIBO WUHENG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510206492.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the molding strength of the molecular sieve as a catalyst support is low, and a binder is required to increase the strength, but this will introduce impurities and reduce the content of the molecular sieve, affecting the activity.

Method used

Nanosilicon dioxide and modified graphene oxide are used as reinforced adhesives to improve the strength and bonding effect of the molecular sieve by forming a tight and complex cross-linking network, while maintaining the activity of the molecular sieve pore structure.

Benefits of technology

The mechanical strength and usage performance of the catalyst support are significantly improved, the impurities problems introduced by the binder are avoided, and the activity of the molecular sieve pore structure is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680619A_ABST
    Figure CN119680619A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst carriers, and particularly relates to a high-strength catalyst carrier and a preparation method thereof.The high-strength catalyst carrier is prepared from, by weight, 60-100 parts of molecular sieve raw powder, 40-80 parts of pseudo-boehmite and 15-30 parts of reinforcing adhesive; the reinforced adhesive comprises the following components in parts by weight: 10-20 parts of nano silicon dioxide slurry; 11 to 19 parts of modified graphene oxide; 3-5 parts of an anti-cracking agent; the nano silicon dioxide and the modified graphene oxide are used as reinforcing main bodies, the strength of the molecular sieve is effectively improved, the pseudo-boehmite colloid is uniformly coated on the surface of the molecular sieve to form a coating body, and the active state of the pore structure of the molecular sieve can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst carriers, and particularly relates to a high-strength catalyst carrier and a preparation method thereof. Background Art

[0002] Molecular sieve is a material containing precise and single tiny pores. The interior of its crystal pores has strong polarity and Coulomb field, and it exhibits strong adsorption capacity for polar molecules (such as water) and unsaturated molecules. The pores of molecular sieves are uniform in diameter. These pores can adsorb molecules smaller than their diameters into the interior of the pores, and have preferential adsorption capacity for polar molecules and unsaturated molecules. Therefore, it can separate molecules with different degrees of polarity, saturation, molecular sizes and boiling points, that is, it has the function of "screening" molecules.

[0003] The chemical formula of pseudo-boehmite is AlOOH·nH2O, where n=0.08-0.62. It is non-toxic, tasteless, odorless, and is in the form of a wet colloid or a dry powder. It has the characteristics of high specific surface area and large pore volume. It is widely used as a catalyst carrier, catalyst, adsorbent, coating additive, high-grade ceramics, grinding and polishing materials, cosmetic fillers, etc. It is a type of material with broad development prospects.

[0004] As for how to improve the strength of the catalyst, the technicians have done a lot of work. For example, the Chinese patent application document with application publication number CN103623858A discloses a catalytic cracking catalyst and a preparation method thereof, which comprises: mixing and slurrying pseudo-boehmite, molecular sieve, aluminum sol and silica sol binder to form a catalyst slurry, then spray drying, and then washing and drying to obtain a finished catalyst. The three binders of pseudo-boehmite, aluminum sol and silica sol are used as a composite binder, which improves the strength of the catalyst to a certain extent.

[0005] In the production process of carriers using molecular sieves as raw materials, since the molding strength of the molecular sieve material itself is very low, a certain amount of binder needs to be added to achieve the strength required by the product. Although the added binder can provide strength, it will cause other problems, such as introducing other impurities into the carrier, reducing the content of the molecular sieve and affecting the activity. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a high-strength catalyst carrier and a preparation method thereof to solve the above-mentioned problems in the background technology.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A high-strength catalyst carrier, the raw materials include the following components by weight: 60-100 parts of molecular sieve powder, 40-80 parts of pseudo-boehmite, and 15-30 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 10-20 parts of nano silicon dioxide slurry; 11-19 parts of modified graphene oxide; and 3-5 parts of an anti-cracking agent.

[0008] By adopting the above structural scheme, nano-silicon dioxide and modified graphene oxide are used as the reinforcing body to effectively improve the strength of the molecular sieve; Furthermore, the nano-silica slurry comprises the following components by weight: 12-23 parts of nano-silica dispersion; 10-19 parts of polymethyl methacrylate; 8-11 parts of polyethylene glycol; and 13-22 parts of polyvinyl butyral. In the nano-silica slurry, the polyethylene glycol in the mixed resin of polymethyl methacrylate, polyethylene glycol and polyvinyl butyral is dissolved and removed by water, and a continuously distributed pore structure is formed on the surface of the molecular sieve. These fine pore structures provide interlacing points for the anti-cracking agent, so that the polypropylene fibers in the anti-cracking agent are interlaced with the modified graphene oxide and the nano-silica slurry molecular sieve to form a tight and complex cross-linked network, which mixes and bonds the molecular sieve mixture system; while having a good bonding effect, it also improves the mechanical strength of the carrier.

[0009] The present invention is further configured that the raw materials include the following components by weight: 70-89 parts of molecular sieve powder, 50-68 parts of pseudo-boehmite, and 21-27 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 11-18 parts of nano-silicon dioxide slurry; 13-17 parts of modified graphene oxide; 4-5 parts of anti-cracking agent; the anti-cracking agent comprises the following components by weight: 13-21 parts of polypropylene fiber and 16-20 parts of glass fiber powder.

[0010] By adopting the above technical solution, the content range of each component in the molecular sieve mixture system is further limited, so that the various components in the molecular sieve mixture system can achieve a better ratio, further improving the performance and strength of the molecular sieve.

[0011] The molecular sieve is REUSY, so that the pseudo-boehmite colloid is evenly wrapped on the surface of the molecular sieve to form a coating, which can maintain the active state of the molecular sieve pore structure. As a thermosetting material, glass fiber powder has excellent strength. The high strength, acid resistance, alkali resistance, and anti-microbial properties of polypropylene fiber are used to improve the crack resistance of the molecular sieve mainly through mechanical action.

[0012] The present invention is further configured that the raw materials include the following components by weight: 80 parts of molecular sieve powder, 60 parts of pseudo-boehmite, and 25 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 17 parts of nano-silicon dioxide slurry; 14 parts of modified graphene oxide; and 4 parts of an anti-cracking agent.

[0013] By adopting the above technical solution, the content range of each component in the molecular sieve mixture system is further limited, so that the various components in the molecular sieve mixture system can achieve a better ratio, further improving the performance and strength of the molecular sieve.

[0014] The present invention is further configured that the preparation method of the nano-silicon dioxide slurry comprises the following steps: the first step; preparing a nano-silicon dioxide dispersion; uniformly mixing a raw material containing silicon dioxide (silicon source), water, a structure directing agent, an alkali or an acid in a certain proportion, putting it into a pressure-resistant reactor and sealing it, then heating it to 100-220°C and keeping the temperature constant for 5 hours to 10 days. After the reaction is completed, the reactor is quickly cooled, the reaction product is washed with water or dilute acid to a pH of 8-11, and dried to obtain a raw powder. The raw powder or the product formed by adding a binder is calcined and activated in a muffle furnace or a tubular furnace to obtain nano-silicon dioxide crystals; the nano-silicon dioxide crystals are added to a mixed solution of 3-(methacryloyloxy)propyltrimethoxysilane and butyl acetate, and reacted at 70-75°C for 3-4 hours to obtain a nano-silicon dioxide dispersion; The second step is to mix polymethyl methacrylate, polyethylene glycol and polyvinyl butyral at 190-195°C for 10-15 minutes, add nano-silicon dioxide dispersion and continue stirring for 10-15 minutes to obtain nano-silicon dioxide slurry; the preparation method of polymethyl methacrylate is to add methyl methacrylate, vinyltrimethylsilane and azobisisobutyronitrile to tetrahydrofuran, react at 80-85°C for 4-5 hours under a nitrogen atmosphere to obtain polymethyl methacrylate.

[0015] The present invention is further configured that the preparation method of the modified graphene oxide comprises: ultrasonically dispersing graphene oxide in deionized water, adding didodecyl dimethyl ammonium bromide solution, stirring evenly, adding isophthalonitrile, stirring evenly, standing, removing the supernatant, purifying, and obtaining modified graphene oxide.

[0016] Another object of the present invention is to provide a method for preparing a high-strength catalyst carrier, comprising the following steps: The first step is to put the molecular sieve raw powder, pseudo-boehmite and reinforcing binder into a mixer, stir at a speed of 800-900 rpm for 40±5min, and mix thoroughly to obtain a premixed powder; The second step is to put the premixed powder into the ball forming machine, rotate the ball forming machine at a speed of 20±2 rpm, and spray water mist into the premixed powder at a speed of 0.5±0.1m / S to obtain prefabricated pellets of a specified diameter; Step 3: Degrease the prefabricated pellets in 50-55°C water for 2-2.5 hours; Step 4: Place the prefabricated pellets in the third step into a high-temperature activation machine and activate them at 500±20°C to obtain a molecular sieve with a water content of 5-6% by mass.

[0017] The prefabricated pellets are degreased in water. On the one hand, the polyethylene glycol in the mixed resin of polymethyl methacrylate, polyethylene glycol and polyvinyl butyral is dissolved and removed by water, and a continuously distributed pore structure is formed on the surface of the molecular sieve. These fine pore structures provide interlacing points for the polypropylene fibers, so that the polypropylene fibers are interlaced with the modified graphene oxide and the nano-silica slurry molecular sieve to form a tight and complex cross-linked network, which mixes and bonds the molecular sieve mixture system; it has a good bonding effect and also improves the mechanical strength of the carrier.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Nano-silicon dioxide and modified graphene oxide are used as the reinforcing body to effectively improve the strength of the molecular sieve, so that the pseudo-boehmite colloid is evenly wrapped on the surface of the molecular sieve to form a coating, which can maintain the active state of the molecular sieve pore structure; 2. The prefabricated pellets are degreased in water, and a continuously distributed pore structure is formed on the surface of the molecular sieve. These fine pore structures provide interlacing points for the polypropylene fibers, so that the polypropylene fibers are interlaced with the modified graphene oxide and the nano-silica slurry molecular sieve to form a tight and complex cross-linked network, which mixes and bonds the molecular sieve mixture system; it has a good bonding effect and also improves the mechanical strength of the carrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A statistical diagram of the lateral pressure strength test results of a high-strength catalyst carrier of the present invention; Figure 2 This is a statistical diagram of the wear test results of a high-strength catalyst carrier of the present invention; DETAILED DESCRIPTION The present invention is further described in detail below in conjunction with the examples. The raw materials of the examples and comparative examples of the present invention are all commercially available unless otherwise specified.

[0020] Embodiment 1: A high-strength catalyst carrier, the raw materials include the following components by weight: 60 parts of molecular sieve powder, 40 parts of pseudo-boehmite, and 15 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 10 parts of nano-silicon dioxide slurry; 11 parts of modified graphene oxide; and 3 parts of an anti-cracking agent.

[0021] The anti-cracking agent includes the following components by weight: 13 parts of polypropylene fiber and 16 parts of glass fiber powder; the nano-silica slurry includes the following components by weight: 12 parts of nano-silica dispersion liquid; 10 parts of polymethyl methacrylate; 8 parts of polyethylene glycol; and 13 parts of polyvinyl butyral.

[0022] Embodiment 2: A high-strength catalyst carrier, the raw materials include the following components by weight: 70 parts of molecular sieve powder, 50 parts of pseudo-boehmite, and 21 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 11 parts of nano-silicon dioxide slurry; 13 parts of modified graphene oxide; and 4 parts of an anti-cracking agent; wherein the anti-cracking agent comprises the following components by weight: 15 parts of polypropylene fiber and 17 parts of glass fiber powder; the nano-silicon dioxide slurry comprises the following components by weight: 17 parts of nano-silicon dioxide dispersion; 15 parts of polymethyl methacrylate; 9 parts of polyethylene glycol; and 16 parts of polyvinyl butyral.

[0023] Embodiment three: A high-strength catalyst carrier, the raw materials include the following components by weight: 80 parts of molecular sieve powder, 60 parts of pseudo-boehmite, and 25 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 17 parts of nano-silicon dioxide slurry; 14 parts of modified graphene oxide; and 4 parts of an anti-cracking agent; wherein the anti-cracking agent comprises the following components by weight: 20 parts of polypropylene fiber and 18 parts of glass fiber powder; the nano-silicon dioxide slurry comprises the following components by weight: 23 parts of nano-silicon dioxide dispersion; 19 parts of polymethyl methacrylate; 10 parts of polyethylene glycol; and 20 parts of polyvinyl butyral.

[0024] Embodiment 4: A high-strength catalyst carrier, the raw materials include the following components by weight: 89 parts of molecular sieve powder, 68 parts of pseudo-boehmite, and 27 parts of reinforcing binder; The reinforcing adhesive comprises the following components by weight: 18 parts of nano-silicon dioxide slurry; 17 parts of modified graphene oxide; and 5 parts of an anti-cracking agent; wherein the anti-cracking agent comprises the following components by weight: 21 parts of polypropylene fiber and 20 parts of glass fiber powder; the nano-silicon dioxide slurry comprises the following components by weight: 23 parts of nano-silicon dioxide dispersion; 19 parts of polymethyl methacrylate; 11 parts of polyethylene glycol; and 21 parts of polyvinyl butyral.

[0025] Embodiment five: A high-strength catalyst carrier, the raw materials include the following components by weight: 100 parts of molecular sieve powder, 80 parts of pseudo-boehmite, and 30 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 20 parts of nano-silicon dioxide slurry; 19 parts of modified graphene oxide; and 5 parts of an anti-cracking agent; wherein the anti-cracking agent comprises the following components by weight: 21 parts of polypropylene fiber and 20 parts of glass fiber powder; and the nano-silicon dioxide slurry comprises the following components by weight: 23 parts of nano-silicon dioxide dispersion; 19 parts of polymethyl methacrylate; 11 parts of polyethylene glycol; and 22 parts of polyvinyl butyral.

[0026] Embodiment six: A high-strength catalyst carrier, the raw materials include the following components by weight: 100 parts of molecular sieve powder, 90 parts of pseudo-boehmite, and 30 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 20 parts of nano-silicon dioxide slurry; 19 parts of modified graphene oxide; and 5 parts of an anti-cracking agent; wherein the anti-cracking agent comprises the following components by weight: 21 parts of polypropylene fiber and 20 parts of glass fiber powder; and the nano-silicon dioxide slurry comprises the following components by weight: 23 parts of nano-silicon dioxide dispersion; 19 parts of polymethyl methacrylate; 11 parts of polyethylene glycol; and 22 parts of polyvinyl butyral.

[0027] Embodiment seven: The preparation method of nano-silicon dioxide slurry comprises the following steps: the first step; preparing nano-silicon dioxide dispersion; mixing raw materials (silicon source), water, structure directing agent, alkali or acid containing silicon dioxide in a certain proportion, putting them into a pressure-resistant reactor and sealing them, then heating them to 100-220°C and keeping the temperature constant for 5 hours to 10 days. After the reaction is completed, the reactor is quickly cooled, the reaction product is washed with water or dilute acid to a pH of 8-11, and dried to obtain raw powder. The raw powder or the product formed by adding a binder is calcined and activated in a muffle furnace or a tube furnace to obtain nano-silicon dioxide crystals; adding the nano-silicon dioxide crystals to a mixed solution of 3-(methacryloyloxy)propyltrimethoxysilane and butyl acetate, reacting at 70-75°C for 3-4 hours to obtain nano-silicon dioxide nano-silicon dioxide dispersion; The second step is to mix polymethyl methacrylate, polyethylene glycol and polyvinyl butyral at 190-195°C for 10-15 minutes, add nano-silicon dioxide dispersion and continue stirring for 10-15 minutes to obtain nano-silicon dioxide slurry; the preparation method of polymethyl methacrylate is to add methyl methacrylate, vinyltrimethylsilane and azobisisobutyronitrile to tetrahydrofuran, react at 80-85°C for 4-5 hours under a nitrogen atmosphere to obtain polymethyl methacrylate.

[0028] Embodiment eight: A method for preparing a high-strength catalyst carrier comprises the following steps: The first step is to put the molecular sieve raw powder, pseudo-boehmite and reinforcing binder into a mixer, stir at a speed of 800-900 rpm for 40±5min, and mix thoroughly to obtain a premixed powder; The second step is to put the premixed powder into the ball forming machine, rotate the ball forming machine at a speed of 20±2 rpm, and spray water mist into the premixed powder at a speed of 0.5±0.1m / S to obtain prefabricated pellets of a specified diameter; Step 3: Degrease the prefabricated pellets in 50-55°C water for 2-2.5 hours; Step 4: Place the prefabricated pellets in the third step into a high-temperature activation machine and activate them at 500±20°C to obtain a molecular sieve with a water content of 5-6% by mass.

[0029] Comparative Example 1: Compared with Example 1, the molecular sieve powder in the raw material is 60 parts, and the pseudo-boehmite is 90 parts. The preparation method refers to Example 7 and Example 8.

[0030] Comparative Example 2: Compared with Example 1, the raw materials include 60 parts of molecular sieve powder and 100 parts of pseudo-boehmite, and the preparation method is the same as that of Example 7 and Example 8.

[0031] Comparative Example 3: Compared with Example 1, the molecular sieve powder in the raw material is 60 parts, and the pseudo-boehmite is 20 parts. The preparation method refers to Example 7 and Example 8.

[0032] Comparative Example 4: Compared with Example 1, no reinforcing adhesive is added, and the preparation method is the same as that of Example 7 and Example 8.

[0033] Comparative Example 5: Compared with Example 8, a method for preparing a high-strength catalyst carrier comprises the following steps: first, placing the molecular sieve raw powder, pseudo-boehmite and reinforcing binder into a mixer, stirring for 40±5 min at a speed of 800-900 rpm, and fully mixing to obtain a premixed powder; The second step is to put the premixed powder into the ball forming machine, rotate the ball forming machine at a speed of 20±2 rpm, and spray water mist into the premixed powder at a speed of 0.5±0.1m / S to obtain prefabricated pellets of a specified diameter; The third step: placing the prefabricated pellets in the third step into a high-temperature activation machine, activating them at 500±20°C to obtain a molecular sieve with a water content of 5-6% by mass.

[0034] Comparative Example 6: Compared with Example 1, no anti-cracking agent is added to the reinforced adhesive, and the preparation method is the same as that of Examples 7 and 8.

[0035] Performance testing The present invention firstly prepares a reinforced adhesive by the preparation method of Example 7 and the formula of Example 1 to Example 6, and then prepares a high-strength catalyst carrier by the preparation method of Example 8 and the formula of Example 1 to Example 6, and prepares Comparative Examples 1 to Comparative Examples 6 at the same time, and then uses a particle strength tester to measure the average lateral compressive strength of N carrier samples according to HG / T2782-2011 (N=20). The relevant test results are as follows: Figure 1 The ZYLL-1B catalyst wear index tester was used to test the wear index according to the standard "NB / SHT0964-2017 Straight tube method for determination of wear index of catalytic cracking catalysts". The relevant test results are shown in the figure. Figure 2 shown.

[0036] Results Analysis Combination Figure 1 From the analysis of Examples 1 to 8 and Comparisons 5 and 6, it can be seen that the strength of the catalyst carrier without the addition of an anti-cracking agent is significantly lower than the strength of the catalyst carrier with the addition of an anti-cracking agent. At the same time, it can be seen that in the steps of the preparation method of the high-strength catalyst carrier, the strength of the catalyst carrier without water-soluble degreasing is lower than the strength of the catalyst carrier with water-soluble degreasing. The prefabricated pellets are water-soluble degreased in water, and a continuously distributed pore structure is formed on the surface of the molecular sieve. These fine pore structures provide interlacing points for the polypropylene fibers, so that the polypropylene fibers are interlaced with the modified graphene oxide and the nano-silica slurry molecular sieve to form a tight and complex cross-linked network, which mixes and bonds the molecular sieve mixture system; while having a better bonding effect, it also improves the mechanical strength of the carrier.

[0037] Combination Figure 2 It can be seen from the analysis of Examples 1 to 8 and Comparisons 5 and 6 that the wear index of the catalyst carrier without adding an anti-cracking agent is significantly higher than the wear index of the catalyst carrier with adding an anti-cracking agent. The wear index of the catalyst carrier without water-soluble degreasing is greater than the wear index of the catalyst carrier with water-soluble degreasing.

[0038] The above are only embodiments of the present invention, and the circuits, electronic components and modules involved are all prior art, which can be fully implemented by those skilled in the art. It is needless to say that the content protected by this application does not involve improvements to software and methods. The common sense such as the known specific structures and characteristics in the scheme is not described in detail here. Ordinary technicians in the relevant field know all the common technical knowledge in the technical field of the invention before the application date or priority date, can obtain all the prior art in the field, and have the ability to apply conventional experimental means before that date. Ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the scope of protection of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A high-strength catalyst carrier, characterized in that: The raw materials include the following components by weight: 60-100 parts of molecular sieve powder, 40-80 parts of pseudo-boehmite, and 15-30 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 10-20 parts of nano-silicon dioxide slurry; 11-19 parts of modified graphene oxide; 3-5 parts of anti-cracking agent.

2. A high-strength catalyst carrier according to claim 1, characterized in that: The raw materials include the following components by weight: 70-89 parts of molecular sieve powder, 50-68 parts of pseudo-boehmite, and 21-27 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 11-18 parts of nano silicon dioxide slurry; and 13-17 parts of modified graphene oxide.

3. A high-strength catalyst carrier as claimed in claim 2, characterized in that: The raw materials include the following components by weight: 80 parts of molecular sieve powder, 60 parts of pseudo-boehmite, and 25 parts of reinforcing adhesive; The reinforcing adhesive comprises the following components by weight: 17 parts of nano-silicon dioxide slurry; 14 parts of modified graphene oxide; and 4 parts of an anti-cracking agent.

4. A high-strength catalyst carrier as claimed in claim 3, characterized in that: The anti-cracking agent comprises the following components by weight: 13-21 parts of polypropylene fibers and 16-20 parts of glass fiber powder.

5. A high-strength catalyst carrier as claimed in claim 4, characterized in that: The nano-silicon dioxide slurry comprises the following components by weight: 12-23 parts of nano-silicon dioxide dispersion; 10-19 parts of polymethyl methacrylate; 8-11 parts of polyethylene glycol; Polyvinyl butyral 13-22 parts.

6. A high-strength catalyst carrier as claimed in claim 5, characterized in that: The preparation method of the nano silicon dioxide slurry comprises the following components; The first step is to prepare a nano-silicon dioxide dispersion; The second step is to mix polymethyl methacrylate, polyethylene glycol and polyvinyl butyral at 190-195°C for 10-15 minutes, add the nano-silicon dioxide dispersion and continue stirring for 10-15 minutes to obtain a nano-silicon dioxide slurry.

7. A high-strength catalyst carrier according to claim 6, characterized in that: The method for preparing a nano-silicon dioxide dispersion comprises: uniformly mixing a raw material containing silicon dioxide, water, a structure directing agent, and an alkali or an acid in a certain proportion, putting the mixture into a pressure-resistant reactor and sealing the mixture, then heating the mixture to 100-220° C. and keeping the temperature constant for 5 hours to 10 days; after the reaction is completed, rapidly cooling the reactor, washing the reaction product with water or diluted acid until the pH value is 8-11, drying the reaction product to obtain a raw powder, and calcining and activating the product after the raw powder is formed in a muffle furnace or a tube furnace to obtain nano-silicon dioxide crystals; and adding the nano-silicon dioxide crystals to a mixed solution of 3-(methacryloyloxy)propyltrimethoxysilane and butyl acetate, reacting the mixture at 70-75° C. for 3-4 hours to obtain a nano-silicon dioxide dispersion.

8. A high-strength catalyst carrier as claimed in claim 6, characterized in that: The method for preparing polymethyl methacrylate comprises: adding methyl methacrylate, vinyl trimethylsilane and azobisisobutyronitrile into tetrahydrofuran, reacting at 80-85° C. for 4-5 hours under a nitrogen atmosphere to obtain polymethyl methacrylate.

9. A high-strength catalyst carrier according to claim 1, characterized in that: The preparation method of the modified graphene oxide comprises: ultrasonically dispersing graphene oxide in deionized water, adding didodecyl dimethyl ammonium bromide solution, stirring evenly, adding isophthalonitrile, stirring evenly, standing, removing supernatant, purifying, and obtaining modified graphene oxide.

10. A method for preparing a high-strength catalyst carrier according to any one of claims 1 to 9, characterized in that: The following steps are involved: first step; Put the molecular sieve raw powder, pseudo-boehmite and reinforcing binder into a mixer, stir at a speed of 800-900 rpm for 40±5 min, and mix thoroughly to obtain a premixed powder; The second step is to put the premixed powder into the ball forming machine, rotate the ball forming machine at a speed of 20±2 rpm, and spray water mist into the premixed powder at a speed of 0.5±0.1m / S to obtain prefabricated pellets of a specified diameter; Step 3: Degrease the prefabricated pellets in 50-55°C water for 2-2.5 hours; Step 4: Place the prefabricated pellets in the third step into a high-temperature activation machine and activate them at 500±20°C to obtain a molecular sieve with a water content of 5-6% by mass.

Citation Information

Patent Citations

  • Catalytic cracking catalyst and preparation method

    CN103623858A

  • Preparation method of catalyst for deep hydrogenation treatment of high-nitrogen distillate oil

    CN102343274A

  • Carbon hollow sphere material with hierarchical porous structure and preparation method thereof

    CN103613085A

  • Wax oil hydrogenation catalyst, and preparation method thereof

    CN108452845A

  • Enhanced molecular sieve and preparation method thereof

    CN111362277A

Cited By

  • Preparation method of molecular sieve catalyst composite carrier

    CN120790214A

  • Preparation method of molecular sieve catalyst composite carrier

    CN120790214B